Fools of fortune - Trevor, William 1928-2016 (Viking Pr., 1983)
William Quinton, a young Irishman who survived the 1918 Irish "troubles," fell in love with a beautiful English cousin. Not until fifty years later did he learn that they have a child.
Keywords: Families -- Ireland -- Fiction; Irland; Domestic fiction